2015
DOI: 10.1145/2829988.2787484
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Control for Large-Scale RDMA Deployments

Abstract: Modern datacenter applications demand high throughput (40Gbps) and ultra-low latency (< 10 μs per hop) from the network, with low CPU overhead. Standard TCP/IP stacks cannot meet these requirements, but Remote Direct Memory Access (RDMA) can. On IP-routed datacenter networks, RDMA is deployed using RoCEv2 protocol, which relies on Priority-based Flow Control (PFC) to enable a drop-free network. However, PFC can lead to poor application performance due to problems like head-of-line blocking and unfairness. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(148 citation statements)
references
References 26 publications
0
138
0
Order By: Relevance
“…Note that of necessity our comparison is for two different host software stacks, as DCTCP runs in an optimized kernel without PFC support whereas TIMELY is used with OS-bypass messaging. We did not implement DCTCP in OS-bypass environment due to NIC firmware limitations on processing ECN feedback [48]. We set the switch ECN marking threshold to K = 80 KB.…”
Section: Small-scale Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that of necessity our comparison is for two different host software stacks, as DCTCP runs in an optimized kernel without PFC support whereas TIMELY is used with OS-bypass messaging. We did not implement DCTCP in OS-bypass environment due to NIC firmware limitations on processing ECN feedback [48]. We set the switch ECN marking threshold to K = 80 KB.…”
Section: Small-scale Experimentsmentioning
confidence: 99%
“…TCP-Bolt [14] uses modified DCTCP algorithm within the kernel TCP stack. DCQCN [48] uses a combination of ECN markings with a QCN-inspired rate-based congestion control algorithm implemented in the NIC. Evaluations demonstrate that it addresses the HoL blocking and unfairness problems with PFC, thus making RoCE viable for largescale deployment.…”
Section: Related Workmentioning
confidence: 99%
“…A distributed scheme may be implemented as part of the end-hosts, switches, or both. Some recent distributed traffic control schemes include those presented in [8], [79], [87], [99], [100].…”
Section: A Distributedmentioning
confidence: 99%
“…To address this, most data center operators add some form of end-to-end congestion control to avoid triggering pause frames. Two examples are DCQCN [38] and HPCC [22]; these use sophisticated control theory to rate-limit individual flows to better manage resources in the middle of the network.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce HoL-blocking, researchers and data center operators have proposed several end-to-end congestion avoidance systems that aim to reduce buffer occupancy and thus the need for PFC pause frames. Timely [26], DCQCN [38], and HPCC [22] monitor gather information from the network in response to packet transmissions to gate how quickly to send additional packets. Because earlier results have shown that DCQCN outperforms Timely [22,39], we focus our comparison on the later two.…”
Section: Introductionmentioning
confidence: 99%